OPTIMISATION OF PROGRAM BUDGET PERFORMANCE AMONG NOT-FOR-PROFIT ORGANISATIONS IN UGANDA: A CASE OF CIVIL SOCIETY IN UGANDA SUPPORT PROGRAMME - Godwin Oketcho; Festo Nyende Tusubira (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
This study set to establish the determinants of budget performance in Civil Society in Uganda Support Programme (CUSP) by the German Agency for International Cooperation in Uganda (GIZ-Uganda). We focused on implementing partners (IP) related determinants as budgetary control, leadership/ governance, organization structure, and of human resource. The study adopted a cross-sectional research design based on samples drawn from across 127 IPs that closed their contracts with CUSP. The unit of observation comprised 127 program coordinators, 127 finance staff, and 127 service extension of IPs’ staff, with a population of 381 staff. A two-stage sampling technique was adopted first, stratified sampling to select staff category amongst the IPs, then purposive sampling to select respondents within the staff categories. An online semi-structured questionnaire was used to collect data. Results show that budgetary control significantly and negatively affects budget performance however, leadership and organisational structure have a significant positive influence on budget performance and human resources did not have any influence. This implies that management of IPs, IDAs and other similar organizations should ensure they have good leadership or governance and organization structures besides investing in budgetary control through policy framework that can translate to effective budget performance.